answersLogoWhite

0


Best Answer

(2n+3)(n+1)=2n2+5n+3.

User Avatar

Wiki User

โˆ™ 2010-01-03 21:15:19
This answer is:
๐Ÿ™
0
๐Ÿคจ
0
๐Ÿ˜ฎ
0
User Avatar
Study guides

Algebra

20 cards

A polynomial of degree zero is a constant term

The grouping method of factoring can still be used when only some of the terms share a common factor A True B False

The sum or difference of p and q is the of the x-term in the trinomial

A number a power of a variable or a product of the two is a monomial while a polynomial is the of monomials

โžก๏ธ
See all cards
3.7
โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…
323 Reviews

Add your answer:

Earn +20 pts
Q: How do you factorise 2nxn plus 5n plus 3?
Write your answer...
Submit
Related questions

How do you factorise 3t plus 9?

It is: 3(t+3)


What is 5n plus 3 plus 4n equals 30?

N=3.


What is 4n-3 plus 5n-8?

-2n


How do you factorise xy plus 3x?

the answer is x(3+y)


How do you factorise 3x plus 6?

It is: 3(x+2)


How do you factorise 24x plus 18?

It is: 6(4x+3)


How do you factorise 3a2 plus 9a?

It is 3a(a+3) when factored


5n plus 3 equals 14-6n what is n?

5n + 3 = 14 - 6n <=> 5n +6n = 14 - 3 <=> 11n = 11 => n = 11/11 = 1


Factorise x2 plus 8x plus 15?

(x+5)(x+3)


3N plus 2N plus 3?

5N + 3 Just add the Ns and put +3 on the end!


How do you factorise 6y plus 15?

It is 3(2y+5) when factorised


Factorise 5x squared plus 17x plus 6?

(5x + 2)(x + 3)


8n plus 12-5n equals 21?

n=3


What is 5n plus 9 equals 2n?

Subract 5n from both sides and you get 9=-3n, then divide bother sides by -3 and you get n= -3


2n plus 3 equals 5n-2?

n=1 2/3


What does n plus 4n-3 equals?

1


How do you factorise 4x2 plus 5x - 6?

(4x-3)(x+2)


Factorise x2 - 10x plus 21?

(x-7)(x-3)


What is the answer when you factorise p2 plus 3p?

p2 + 3p = p (p + 3)


How do you factorise 4x plus 6?

It is 2(2x+3) when factorised


How do you factorise 4xcube plus 20xsquare plus 2x - 3?

You cannot since the expression does not have rational roots.


What is 5n plus 1 equals 10 plus 2n?

5n + 1 = 10 + 2n5n - 2n + 1 - 1 = 10 - 1 + 2n - 2n3n = 93n/3 = 9/3n = 3


How do you factor mn - 15 plus 3m - 5n?

mn - 15 + 3m - 5n Rearranging: mn + 3m - 5n - 15 = m(n + 3) - 5(n + 3) = (m - 5)*(n + 3)


5n-4 equals 8 plus n?

5n - n = 8 + 4 ie 4n = 12 so n = 3


How do you factorise this expression - 2x plus 6?

2x + 6 = 2(x+3)